INDONESIAN LEGAL SYSTEM AND ITS DEVELOPMENT - Simon Simon (Proceeding International Seminar of Islamic Studies, 2023)
The development of law in Indonesia is inseparable from the history that has been going on for quite a long time. If you look at this long history, the laws in Indonesia originate from the Netherlands, which once colonized Indonesia. It is undeniable that Indonesia has adopted the law originating from the Netherlands. The development of Indonesian national law is something that the government inevitably has to do in order to form a national law that is rooted in all levels of society. The development of Indonesia's national law, which is currently heavily influenced by external elements, is as much as possible in order to maintain the material legal sources of Indonesian laws. The development of national law that focuses on the Indonesian spirit and Indonesian taste can only be carried out with the consensus of all elements of the nation.